Optimization of Case Manager in Increasing Patient Satisfaction and Reducing Heart Patient Care Costs at Mitra Mulia Husada Hospital - Felix Kasim (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Heart disease is a major cause of morbidity and mortality in Indonesia, with increasing health care costs. Optimizing the role of case managers is seen as a potential solution to improve service quality while reducing care costs. This study aims to analyze the effect of optimizing case managers in improving patient satisfaction and reducing care costs in heart disease patients at Mitra Mulia Husada Hospital. This study used a quantitative design with a pre-experimental one-group pretest-posttest approach. Data were collected through a patient satisfaction survey using a SERVQUAL-based instrument and analysis of care cost data from medical record reports before and after the implementation of case managers. The implementation of case managers showed an increase in the average patient satisfaction score from 3.55 to 4.45 (Likert scale 1-5) and a decrease in the average daily cost of care by 20%. In addition, there was a reduction in the length of hospitalization from 7 to 5 days. Optimal implementation of case managers can significantly improve patient satisfaction and efficiency of care costs. These findings support the integration of case managers as an important part of health service management for heart disease patients in hospitals.